Pendampingan Baca Tulis Al Quran bagi Anak-Anak di Lokasi KKN Kelurahan Dodu Kota Bima - Puji Muniarty; Wulandari Wulandari; Ansyarif Ansyarif; Nurchairunisyah Nurchairunisyah; Farah Meinda Sari; Jefrianus Lalung; Adhe Fitrianingsih; Muh Zinedin Zidan; Muamal Tupriatna; Supratman Supratman; Antin Yuliantin; Eby Hidayat; Islahulkhair Islahulkhair; Uswatun Nuraini; Agustina Agustina; Bambang Hermanto; Tauhid Lil Akbar; Ayu Indah Pratiwi Amalia; Wahidah Wahidah; Murniati Murniati; Muhamad Ridwan; Riska Afriani; Esiati Esiati; Arfah Rahmayanti; Rifka Annisa; Sumiati Sumiati; M Muchlis; Maryana Maryana; Nandha Ramdani; Nabila Putri Sakinah; Muh Yuslan; Ari Afriansyah; Dewi Ayu Lestari (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This community service activity is through attracting community participation to allow children to learn the Koran. The objectives of the activity are; as a solution to the limited number of Koran teachers in the midst of a ban on crowding during the COVID-19 pandemic. The coaching program is carried out through assistance in eradicating illiteracy in the Koran through the Iqra method. Initial observations through interviews with religious leaders and several communities stated that children were less interested in the Koran at TPQ because they had to queue for a long time at one Koran teacher so that they felt bored and ended up decreasing their concentration and enthusiasm for learning the Koran. This activity is divided into three classics, namely; Opening activities (early classics), core activities and closing activities (late classics). The existence of a place to learn the Koran at the KKN Post every night, becomes a means to gather and interact with each other, besides being a means to meet other children with one another, it is also very important for the children of Dodu Village. because with this learning facility it can increase knowledge to children, especially in terms of correct and precise reading of the Qur'an through learning Iqra. The existence of the KKN post as an alternative to learning the Koran is very beneficial for children who previously only spent their days playing and with busy parents who sometimes make children less attention from their parents.